The Incidence of Overactive Bladder in KIA Poly Patients at Pauh Health Center in Padang City Using Overactive Bladder Symptoms Score - Bobby Indra Utama; Widayat Widayat; Berriandi Arwan (Universitas Andalas, 2019)
Objective : This study looked at the incidence of overactive bladder (OAB) in KIA poly patients at Pauh Health Center in Padang City using Overactive Bladder Symptomps Score (OABSS).Method : This research is descriptive. The sampling technique was purposive sampling by considering inclusion and exclusion criteria. The inclusion criteria were women of ideal reproductive age (20-35 years) who had given birth spontaneously, were not pregnant, did not suffer from neurological disorders, diabetes, post bladder surgery and or urinary tract infections and were not treated with Overactive Bladder (OAB), while the exclusion criteria are not willing to take part in the study. The study was carried out at the KIA Poly of Pauh City Health Center in Padang during January 2019. The variable in this study was Overactive Bladder (OAB).Result : In this study, 97.22% of respondents experienced complaints of overactive bladder (OAB), (97.14%) experienced an urgent complaint, and only a small percentage (2.86%) of respondents experienced urinary incontinence. The results of this study indicate that respondents who did not experience complaints of overactive bladder (OAB) were respondents with the smallest parity (parity 1). Conclusion : Most respondents experienced complaints of overactive bladder (OAB) and urgency, and only a small proportion of respondents experienced urinary incontinence. The results of this study indicate that respondents who did not experience complaints of overactive bladder (OAB) were respondents with the smallest parity (parity 1).Keywords: overactive bladder (OAB), Urgensi,inkontinensia urin, Overactive Bladder Symptom Scores (OABSS)